The impact of flexible aggregate strategy in learning some of gym skills - Abdulla, M. H.; Hussein, G. L.; Hasan, A. J. (Journal of Human Sport & Exercise, 2021)
The aim of the research is to identify the impact of an educational curriculum for the strategy of flexible groups and the traditional method of learning some of the skills of the technical gym for men and to identify the differences between the members of the experimental group that used an educational method for the strategies of flexible groups and members of the control group that used the traditional method in the post test in learning some of the skills of the technical gym of men. The research community was represented by the second stage students in the College of Physical Education and Sports Sciences - Basra University for the academic year 2016-2017, they were (100) students distributed among (6) Sections, and a sample was chosen from that community by (36) students in a simple random way. The sample was divided in to experimental and control groups (18) students for each group. The application of the curriculum for the strategy of flexible groups was launched on 24/2/2019 and at the rate of two educational units per week and finished applying the curriculum on 13/4/2019, after processing the results of per and post tests using appropriate statistical means the researcher concluded the following: The use of both the flexible group strategy and the traditional method has shown a positive effect in learning the skills of the artistic gymnastics under study; The flexible group strategy is better than the traditional method for learning the technical gymnastics skills under study.